A silent health crisis: understanding anemia in Pakistani men - Khan, Shabitul Aisha; Khan, Zoha; Mahmood, Samoon (Journal of the Pakistan Medical Association, 2026)
Dear Editor, we are writing to bring attention to an overlooked public health issue in Pakistan: anaemia in men. The World Health Organisation (WHO) as having haemoglobin (Hb) levels lower than 12.0 and 13.0 g/dL in females and males respectively.1 Anaemia in woman has been heavily discussed in medical literature however, there is a significant lack of detailed discussion for anaemia in men. Anaemia can arise due to a variety of factors which can induce differing clinical features. Common causes of anaemia include iron or vitamin B12 deficiency, blood loss, chronic infections, and genetic factors. Thus, diagnosing and treating anaemia can pose a challenge, especially in demographics in which resources are limited. As a result, a range of complications arise such as immune system dysfunction, decline in neurocognitive abilities, disturbances in the gastrointestinal tract, and regulation of body temperature.2 The scale of this issue is not fully known due to a lack of contemporary, male-focused research. A 2016 study from Karachi reported a high prevalence of 51.4% among men, but a more recent 2023 community-based study in Karachi found anaemia in 22.1% of adults, with male gender being a protective factor. (3) This discrepancy highlights the critical need for updated, nationally representative data specifically for men. (4) The overwhelming focus of research and national nutrition surveys on women of reproductive age and children has created a significant evidence gap regarding the male population. Understanding the prevalence and specific aetiologies of anaemia in men is crucial for several reasons. Beyond the direct impact on individual health and quality of life, chronic anaemia in a large segment of the male workforce can affect national economic productivity. Addressing this requires targeted research to understand the trends, causes, and risk factors among men from diverse sociodemographic and geographic backgrounds in Pakistan. This leads to the pivotal question: why is anaemia not systematically investigated in Pakistani men? A primary reason is that international and national clinical guidelines prioritise screening for high-risk groups, such as pregnant women and children, and do not recommend routine screening for asymptomatic men. Consequently, men are often absent from anaemia-related healthcare discussions unless they present with severe symptoms. Furthermore, in a lower-middle-income country like Pakistan, barriers such as the cost of diagnosis and treatment, lack of awareness, and the perception of anaemia as a "woman’s disease" likely prevent men from seeking care.(4)